Pengenalan Edukasi Seks Anak Usia Dini melalui Media Islamic Busy Book pada Kelompok B di RA Muslimat NU 085 Pulosari - Annisa Nurfadila; Fuad Fitriawan; Mariana Mariana (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The amount of news circulating about sexual harassment involving children is an urgent problem among parents. Therefore, the introduction of sex education must be instilled as early as possible to children so that children are able to protect and fortify themselves. Early childhood education is the foundation for parents and educators to build character and knowledge for children. Through this study, researchers agreed to develop learning media to facilitate educators in delivering material about sex education to early childhood. The type of research used is Research and Development (R&D) with five procedures of the ADDIE model stages which include analysis, design, development, implementation and evaluation. This study involved two lecturers as material experts and media experts, nine teachers or educators as respondents for the assessment of material and media instruments, and group B students at RA Muslimat NU 085 Pulosari as research subjects. Based on the assessment of media experts and respondents through validity and reliability tests, the Islamic Busy Book media is declared valid and reliable. While the assessment of the material experts and respondents through the validity test and reliability test for the material contained in the Islamic Busy Book media was also declared valid and reliable. So that the media and materials that have been developed are suitable for use as learning tools in delivering the introduction of sex education to early childhood in the research site.